Impact of Economic Liberalization in Nepal - A Case of Industrial Growth in the Operating Industries in Butwal - Singh, Bal Krishna Man; Paykuryal, Bishwambher (Nepal Journal of Multidisciplinary Research, 2021)
The economic liberalization can contribute in the economic growth of a country. So, Nepal has been following the policy of economic liberalization since the mid-1980s which was accelerated with the start of 1990s. The study was conducted to identify the impact of economic liberalization on economic growth of industries running in the Butwal area of Nepal. The study had selected 385 respondents from industry, trade and banking sectors. The simple random sampling technique was used to select the respondents. Statistical analysis was done to see the relationship between the respondents. The result shows that there was significant association between the respondents (industrialists, traders, and bankers) in effectiveness of economic liberalization because the p value was less than .05 significant levels. Some of the economic indicators were not changed significantly so future researcher can study on the challenges in effective implementation of economic liberalization in Nepal.